2016
DOI: 10.3329/bccj.v4i2.30030
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Fever induced Myocarditis

Abstract: Dengue is an arthropod-borne viral illness, mostly asymptomatic, but may present with a wide variety of clinical manifestations, from mild febrile illness to severe and fatal disease. Cardiac involvement is a significant yet under-reported one because of lack of awareness. We report a case of myocarditis in Dengue Fever with an intention to create awareness among the physicians.Bangladesh Crit Care J September 2016; 4 (2): 125-127

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…However, recent studies have highlighted the potential involvement of the heart in dengue-related shock [2][3][4][5]. Authors have reported cases of direct cardiac involvement in dengue fever patients, suggesting a plausible connection between cardiac dysfunction and the development of shock [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have highlighted the potential involvement of the heart in dengue-related shock [2][3][4][5]. Authors have reported cases of direct cardiac involvement in dengue fever patients, suggesting a plausible connection between cardiac dysfunction and the development of shock [3,6,7].…”
Section: Introductionmentioning
confidence: 99%